Activity-based teaching of Quran for deaf students in the special education integration program - Dzulkifli, Izuli; Suhid, Asmawati; Mohd Fakhruddin, Fathiyah; Ahmad, Nor Aniza (Universiti Putra Malaysia Press, 2021)
The formal teaching and learning of the Quran for the hearing-impaired students in Malaysia is carried out at Special Education Schools offering Special Education Integration Program, locally known as ‘Program Pendidikan Khas Integrasi’(PPKI). The teaching and learning of the Quran for hearing-impaired students are based on the Special Education Curriculum of the Islamic Education subject. In order to enhance the achievement of deaf students in learning the Quran, teachers need to plan lessons relevant to the content of the learning of the Quran and students’ abilities. The objective of this study was to explore the activitybased teaching, such as reading and memorizing, employed by teachers who were teaching the Quran to deaf students in eight primary schools offering PPKI. This study utilized the qualitative approach in the form of case studies, using the interview technique and document analysis to obtain data. The findings showed the main activities inculcated in the learning of the Quran were reading and writing skills. These activities were carried out individually and in groups based on the different characteristics of the deaf students. Therefore, teachers should be aware of students’ ability levels and the different characteristics of the students’ hearing impairments such as mild, severe, and profoundly deaf so that the planned learning activities could be conducted smoothly during the teaching and learning sessions.